Effect of Nitrate on Biogenic Sulfide Production - Jenneman, Gary E. (1986)
The addition of 59 mM nitrate inhibited biogenic sulfide production in dilute sewage sludge (10% [vol/vol]) amended with 20 mM sulfate and either acetate, glucose, or hydrogen as electron donors. Similar results were found when pond sediment or oil field brines served as the inoculum. Sulfide production was inhibited for periods of at least 6 months and was accompanied by the oxidation of resazurin from its colorless reduced state to its pink oxidized state. Lower amounts of nitrate (6 or 20 mM) and increased amounts of sewage sludge resulted in only transient inhibition of sulfide production. The addition of 156 mM sulfate to bottles with 59 mM nitrate and 10% (vol/vol) sewage sludge or pond sediment resulted in sulfide production. Nitrate, nitrite, and nitrous oxide were detected during periods where sulfide production was inhibited, whereas nitrate, nitrite, and nitrous oxide were below detectable levels at the time sulfide production began. The oxidation of resazurin was attributed to an increase in nitrous oxide which persisted in concentration of about 1.0 mM for up to 5 months. The numbers of sulfate-reducing organisms decreased from 10(6) CFU ml(−1) sludge to less than detectable levels after prolonged incubation of oxidized bottles. The addition of 10 mM glucose to oxidized bottles after 14.5 weeks of incubation resulted in rereduction of the resazurin and subsequent sulfide production. The prolonged inhibition of sulfide production was attributed to an increase in oxidation-reduction potential due to biogenic production of nitrous oxide, which appeared to have a cytotoxic effect on sulfate-reducing populations.